GENE MUTATIONS AND THEIR IMPACT ON HUMAN HEALTH - Kuriyazova Saodat Matkarimovna, Aliqulova Aziza Ulug‘bek qizi, Kudbidinova Gulgina Sherzod qizi (Ethiopian International Journal of Multidisciplinary Research, 2026)
Gene mutations are alterations in the genetic material of living organisms, representing one of the primary causes of hereditary diseases. This article provides a comprehensive analysis of the mechanisms, types, and impact of gene mutations on human health. The study examines the role of mutations in the development of oncological, neurodegenerative, and other hereditary conditions. Furthermore, it discusses advancements in genetic diagnostic methods and therapeutic approaches for mutation-driven diseases. The article aims to establish a crucial scientific foundation for developing strategies to prevent and treat genetic disorders.